The Effect of Biology Module with Scientific Approach Equipped with a Glossary in Discovery Learning Model Against Learning Competencies of Class X Students of SMAN 1 Pariaman - Husnul Mar'i; Ristiono Ristiono; Yosi Laila Rahmi; Yuni Ahda (ATRIUM PENDIDIKAN BIOLOGI, 2019)
This study is based on the problems that exist in SMAN 1 Pariaman, namely: textbooks that are used have not involved students playing an active role in learning, the learning model that is applied is still monotonous, student notebooks are incomplete and textbooks used in schools are not yet available example or images according to the demands of basic competencies to clarify the material description. Efforts can be made is the application of biological modules with a scientific approach equipped with a glossary in Discovery Learning models on the competencies of students in Class X of SMAN 1 Pariaman.The purpose of this study was to determine the effect of biological modules with a scientific approach equipped with a glossary in Discovery Learning models on the competencies of students in Class X of SMAN 1 Pariaman. This study was a quasi-experimental study with a randomized posttest control group design. The study population was tenth-grade students of SMAN 1 Pariaman 2018/2019 academic year consisting of seven classes. The research sample was taken using a purposive sampling technique, the results of which were selected Class X MIPA 2 as the experimental class and Class X MIPA 3 as the control class.The results of data analysis found that the knowledge competencies data was normal and not homogeneous, competencies data on attitudes skill are homogeneous and normal. Hypothesis test results are known that knowledge competencies (7,06>1,67), attitude competencies (0,76<1,67), and skill competencies (0,93<1,67), so it can be concluded that the biological module with a scientific approach is equipped a glossary in Discovery Learning  models has a positive influence on students' knowledge competencies but does not have a positive influence on the competencies of students' attitudes and skills at SMAN 1 Pariaman.